Micelle-Mediated Chemistry in Water for the Synthesis of Drug Candidates - Steven, Alan (Synthesis, 2019)
Micellar reaction conditions, in a predominantly aqueous medium, have been developed for transformations commonly used by synthetic chemists working in the pharmaceutical industry to discover and develop drug candidates. The reactions covered in this review are the Suzuki–Miyaura, Miyaura borylation, Sonogashira coupling, transition-metal-catalysed CAr–N coupling, SNAr, amidation, and nitro reduction. Pharmaceutically relevant examples of these applications will be used to show how micellar conditions can offer advantages in yield, operational ease, amount of waste generated, transition-metal catalyst loading, and safety over the use of organic solvents, irrespective of the setting in which they are used.1 Introduction2 Micelles as Solubilising Agents3 Micelles as Nanoreactors4 Designer Surfactants5 A Critical Evaluation of the Case for Chemistry in Micelles6 Scope of Review7 Suzuki–Miyaura Coupling8 Miyaura Borylation9 Sonogashira Coupling10 Transition-Metal-Catalysed CAr–N Couplings11 SNAr12 Amidation13 Nitro Reduction14 Micellar Sequences15 Summary and Outlook
Keywords: amphiphile; micelle; pharmaceutical; surfactant; Suzuki–Miyaura; TPGS-750-M